Antigenic Structure of Transmissible Gastroenteritis Virus. II. Domains in the Peplomer Glycoprotein - Delmas, B.; Gelfi, J.; Laude, H. (Journal of General Virology, 1986)
Summary The antigenic structure of the peplomer glycoprotein E2 of the porcine transmissible gastroenteritis coronavirus (TGEV) was explored using a panel of 23 hybridoma antibodies (MAbs). The topography of the epitopes was established by means of a competition radioimmunoassay. Four main antigenic sites, termed A, B, C and D, were thus clearly delineated. Most of the neutralization-mediating determinants were found to cluster in the A-B area, which has been shown to be highly conserved among TGEV strains. Cooperative enhancement of binding to sites B and D was observed following attachment of MAbs relevant to site A. Additional epitopes were identified on E2 by MAbs that selectively recognized its intracellular precursor. Functional mapping was also performed using neutralization-resistant variants. Analysis of their reactivity confirmed part of the epitope linkages defined by the first approach. The overall lower frequency of such variants altered at site A suggested that some of the epitopes may play an essential function.
Keywords: epitopes